Frailty syndrome and the risk of vascular dementia: The Italian Longitudinal Study on Aging. Issue 2 (14th December 2012) - Solfrizzi, Vincenzo; Scafato, Emanuele; Frisardi, Vincenza; Seripa, Davide; Logroscino, Giancarlo; Maggi, Stefania; Imbimbo, Bruno P.; Galluzzo, Lucia; Baldereschi, Marzia; Gandin, Claudia; Di Carlo, Antonio; Inzitari, Domenico; et al.
Abstract : Background: Frailty is a clinical syndrome generally associated with a greater risk for adverse outcomes such as falls, disability, institutionalization, and death. Cognition and dementia have already been considered as components of frailty, but the role of frailty as a possible determinant of dementia, Alzheimer's disease (AD), and vascular dementia (VaD) has been poorly investigated. We estimated the predictive role of frailty syndrome on incident dementia and its subtypes in a nondemented, Italian, older population. Methods: We evaluated 2581 individuals recruited from the Italian Longitudinal Study on Aging sample population consisting of 5632 subjects aged 65 to 84 years and with a 3.9‐year median follow‐up. A phenotype of frailty according to a modified measurement of Cardiovascular Health Study criteria was operationalized. Dementia, AD, and VaD were classified using current published criteria. Results: Over a 3.5‐year follow‐up, 65 of 2581 (2.5%) older subjects, 16 among 252 frail individuals (6.3%), of which 9 were affected by VaD (3.6%), developed overall dementia. In a proportional hazards model, frailty syndrome was associated with a significantly increased risk of overall dementia (adjusted hazard ratio: 1.85; 95% confidence interval: 1.01–3.40) and, in particular, VaD (adjusted hazard ratio: 2.68; 95% confidence interval: 1.16–7.17). The risk of AD or other types of dementia did not significantly change in frail individuals in comparison with subjects without frailty syndrome. Conclusion: In our large population‐based sample, frailty syndrome was a short‐term predictor of overall dementia and VaD.